Relatioship between basic composition of magnetic mineral and magnetic suseptibility value of guano from Bau Bau cave East Kalimantan. - Nurul Garnetsya D Rusli (Department of Physics – Universitas Negeri Padang UNP, 2014)
Identification of magnetic susceptibility value and element composition of this research is done by guano sample from Bau-Bau caves in East Borneo. This cave topography is far from human activity and there is no volcano around it. This topography conditions will effects to the transportation process of magnetic mineral into caves area. Magnetic mineral characterization such as magnetic susceptibility and element composition could show the enviromental changes in the cave at the time of guano deposition process. This research aims to determine the elemental composition of the basic constituent asociation of magnetic mineral to the magnetic susceptibility values of guano samples. Determination of magnetic susceptibility value done by using Susceptibility Meter, whereas to determine the element composition we use the X-ray Fluorescences (XRF). Data analisys is done by using the plotting of data from elemental composition of the fourth group in the transition graph. Thus it making visible the relation between the value of the magnetic susceptibility with the basic elements magnetic up the composition of magnetic minerals in perticular Fe, then we could seen the composition of Fe proportional to the magnetic susceptibility value. Fe composition will appears in high presentation on the time of susceptibility value is high and will appears in low presentation when the susceptibility values is low. An the other hand, element composition of the fourth group in the transition except Fe with magnetic susceptibility value is not really appears